The DEVELOPMENT OF SAVONIUS VERTICAL-AXIS WIND TURBINE PROTOTYPE BASED ON MICROCONTROLLER - Zulhajji, Zulhajji; Suhardi, Iwan; Sadri, Abdul Rijal (Jurusan Pendidikan Teknik Elektro, 2025)
This research focuses on the development of a valid prototype of the Savonius vertical axis wind turbine model through a research and development (R&D) approach, using a modified Borg and Gall development model. The study introduces a functional prototype suitable for student learning in renewable energy courses, offering a simpler and more portable alternative to wind energy generation. Student responses showed a positive perception, with 53% stating that the Savonius wind turbine was suitable for the presentation. The results of the questionnaire showed an overall average score of 86%, which was categorized as